Принятие решений при реализации IT-проектов на основе имитационного моделирования - Кошкин, К. В.; Возный, А. М.; Кнырик, Н. Р. (НТУ "ХПИ", 2016)
В статье предложена имитационная модель проекта IT-компании на основе интеграции принципов системной динамики и когнитивного моделирования. Приводятся примеры экспериментов с моделью. Анализируются изменения значений параметров при принятии различных управленческих решений. Представлены результаты экспериментов с моделью: симуляции, оптимизационного эксперимента, эксперимента по методу Монте-Карло, а также анализа чувствительности выходных данных к изменению значений ключевых факторов модели.

The article analyzes the key success factors of IT-projects, which can be influenced. A key factor is the "optimization". Because of the complexity and non-linear dependence between the indicators, the use of any optimization models is not possible. In practice, the analysis is generally limited to a small number of key scenarios. Automation of the process is possible by means of optimization experiments based simulation. The work for this project proposed simulation model IT-companies, based on the principles of integration of system dynamics and cognitive modeling. Shown examples of experiments with model: simulation, optimization of the experiment, an experiment on the Monte Carlo method. Changes in parameter values when making the various administrative decisions has been analyzed. To perform scenario analysis for the input variables are determined by parameters that define their targets. With the help of optimization experiments it is possible to find the values of model parameters under which the simulation results most closely match the specified data. The ways to adapt the input to achieve predictable results has been proposed.
Decision-making in the implementation of IT-projects through simulation
Keywords: управление IT-проектами; модель проекта; квалифицированные кадры; опыт управления; IT-project management; project model; simulation